Residential Irrigation System Rainfall Shutoff Devices, or Rain Sensors: ABE325/AE221, rev. 7/2024 - Dukes, Michael D.; Cárdenas, Bernard (EDIS, 2024)
This publication aims to provide basic information about rain sensors when incorporated into automatic irrigation systems. Written by Michael D. Dukes and Bernard Cardenas, and published by the UF/IFAS Department of Agricultural and Biological Engineering, revised July 2024.